The Role of GeneXpert® for Tuberculosis Diagnostics in Brazil: An Examination from a Historical and Epidemiological Perspective - Tirça Naiara da Silva Iúdice; Marília Lima da Conceição; Artemir Coelho de Brito; Nicole Menezes de Souza; Cristal Ribeiro Mesquita; Ricardo José de Paula Souza e Guimarães; Ismari Perini Furlaneto; Alessandra de Souza Saboia; Maria Cristina da Silva Lourenço; Karla Valéria Batista Lima; Emilyn Costa Conceição (Tropical Medicine and Infectious Disease, 2023)
The rapid molecular test (RMT) performed on the GeneXpert® system is widely used as a control strategy and surveillance technique for tuberculosis (TB). In the region of the Americas, TB incidence is slowly increasing owing to an upward trend in Brazil, which is among the high TB-burden countries (HBCs), ranking in the 19th position. In this context, we aimed to (i) describe the implementation and history of RMT-TB (Xpert® MTB/RIF and Xpert® MTB/RIF Ultra) in Brazil; (ii) to evaluate the national RMT laboratory distribution, TB, and resistance to RIF detection by RMT; and (iii) to correlate these data with Brazilian TB incidence. The quantitative data of Xpert® MTB/RIF and Xpert® MTB/RIF Ultra assays performed in the pulmonary TB investigation from 2014 to 2020 were provided by the Brazilian Ministry of Health. A spatial visualization using ArcGIS software was performed. The Southeast region constituted about half of the RMT laboratories—from 39.4% to 45.9% of the total value over the five regions. Regarding the federal units, the São Paulo state alone represented from 20.2% to 34.1% (5.0 to 8.5 times the value) of RMT laboratories over the years observed. There were significant differences (p < 0.0001) in the frequency of RMT laboratories between all years of the historical series. There was an unequal distribution of RMT laboratories between Brazilian regions and federal units. This alerts us for the surveillance of rapid molecular detection of TB in different parts of the country, with the possibility of improving the distribution of tests in areas of higher incidence in order to achieve the level of disease control recommended by national and worldwide authorities.